Sistem Akuisisi Data Multi Node untuk Irigasi Otomatis Berbasis Wireless Sensor Network - Chaerur Rozikin; Heru Sukoco; Satyanto Krido Saptomo (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
Watering plants is one of farmer’s activities. Most of Indonesian farmers use traditional watering method to water plants. It causes water productivity unmanaged properly and soil moisture level can not be monitored. To resolve these problems, an automatic watering system is developed. This system uses soil moisture sensors which provide real-time data. Data from multiple sensor node will be transmitted through wireless sensor network. LED in actuator node will turn on or off based on lower and upper set point values transmitted from coordinator node. Soil moisture sensors are calibrated using groundwater level to obtain correlation between sensor and groundwater level. Delay, throughput, and packet loss ratio are measured and result 0.2 seconds, 1.6 kbps, and 1.6%, respectively. These values showed that all automatic watering system were well implemented.